A perspective on addressing rancidity in pearl millet : Addressing rancidity in pearl millet - Reddy, Sanjana; D, Sravani; M, Shanthi Priya (Annals of Arid Zone, 2023)
Pearl millet is a boon crop having the inherent capacity to grow under adverse environmental conditions without compromising with the quality and quantity of the grains. Among millets, pearl millet has many health benefits and new variants that are being conventionally cultivated provides a higher level of dietary iron to women. However, off-odour development in flour is one of the major limiting factors in the popularization of pearl millet all over the world. The poor keeping quality of pearl millet flour is due to the oxidative/ hydrolytic rancidity caused by enzymes like lipase and lipoxygenase that hydrolyse triacylglycerol to free fatty acids and lead to rapid deterioration of flour during storage. In this review, the changes observed in nutritional value of pearl millet flour during storage and key biochemical parameters associated with the development of flour rancidity and the genetics controlling rancidity associated traits are discussed